Peran ATLM Dalam Penegakan Diagnosis Anemia Pada Anak Dan Ibu Hamil - Marsudi, La Ode (Program Studi Teknologi Laboratorium Medis, ITKES Wiyata Husada Samarinda, 2022)
Development efforts in the health sector which are being carried out in stages and continuously are aimed at accelerating the attainment of the level of welfare. Indonesia is still prioritizing efforts to improve the health status of mothers and children, especially in groups that are most vulnerable to intimacy, namely pregnant women, childbirth, and babies in the perinatal period. Anaemia in pregnancy results in bleeding. Anaemia is a condition where the number and size of red blood cells or haemoglobin concentration is below the normal limit value, the result of which can interfere with the capacity of the blood to transport oxygen around the body. The prevalence rate of anaemia is still high, namely globally the prevalence of anaemia in pregnant women worldwide is 43.9%. The prevalence of anaemia in pregnant women is estimated in Asia at 49.4%, Africa at 59.1%, America at 28.1% and Europe at 26.1%. The total number of sufferers of anaemia in pregnant women in Indonesia is 70%, meaning that out of 10 pregnant women, as many as 7 people will suffer from anaemia. This community service aims to provide education to the public about how anaemia is experienced, especially in children and pregnant women and the role of ATLM in establishing the diagnosis of anaemia to determine further therapy for anaemia sufferers, especially in children and pregnant women.